Iris color matters in ocular health assessment - Arizcuren, Ana R.; Consejo, Alejandra (Jornada de Jóvenes Investigadores del I3A, 2025)
Corneal transparency, quantified by corneal densitometry (CD), is used in ocular health assessment. This study found that iris color influences CD measurements. Light-colored irises are associated with higher CD values (i.e., lower transparency), suggesting that iris color may introduce bias in CD and affect clinical accuracy.